2016
DOI: 10.1016/j.rmed.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of five clusters of comorbidities in a longitudinal Japanese chronic obstructive pulmonary disease cohort

Abstract: Five clusters of comorbidities were identified in Japanese COPD patients. The clinical characteristics and health-related quality of life were different among these clusters during a follow-up of two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
(40 reference statements)
8
27
0
Order By: Relevance
“…Therefore, we considered asthma patients with CAO but a low smoking history not to be ACO under the proposed criteria. The reported vascular diseases as a comorbidity of COPD are markedly lower in Japan than in other countries, 31 33 and the data of this study were consistent with those of a recent study in Japan. 31 …”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we considered asthma patients with CAO but a low smoking history not to be ACO under the proposed criteria. The reported vascular diseases as a comorbidity of COPD are markedly lower in Japan than in other countries, 31 33 and the data of this study were consistent with those of a recent study in Japan. 31 …”
Section: Discussionsupporting
confidence: 92%
“…Severe COPD exacerbation was defined as one that required hospitalization, including an emergency admission for 24 h [ 24 ]. Comorbid diagnoses were established by clinical history and examination findings based on a review of available medical records [ 20 , 21 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Independent investigators judged the number and severity of exacerbations based on reviews of physicians' medical records, as previously reported [15]. Comorbid diagnoses were established by clinical history and examination findings based on review of available medical records [12,13,16].…”
Section: Assessment Of Clinical Parametersmentioning
confidence: 99%